2022
DOI: 10.1097/gox.0000000000004123
|View full text |Cite
|
Sign up to set email alerts
|

24-hour Perfusion of Porcine Myocutaneous Flaps Mitigates Reperfusion Injury: A 7-day Follow-up Study

Abstract: Background: Static cold storage is the gold standard of preservation in vascularized composite allotransplantation and allows a preservation time of 4–6 hours. Machine preservation is a promising technique for prolonged preservation; however, studies on extended preservation that compare different preservatives are scarce. This study aims to assess the feasibility of 24-hour acellular perfusion and compares different preservation solutions in a porcine myocutaneous flap replantation model. Methods: Six harve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
(63 reference statements)
0
3
0
Order By: Relevance
“…Kruit et al and later our team described the first machine perfusion protocols applied to large animal VCA 27 , 28 , 36 , 39 , 44 46 . Nonetheless, current dynamic hypothermic and SNMP techniques are limited to preservation periods of 24 to 36 h due to factors such as edema and vascular resistance 34 , 47 49 . Supercooling has proven itself a promising technique to overcome these limits and go beyond several days in liver 22 , 50 .…”
Section: Discussionmentioning
confidence: 99%
“…Kruit et al and later our team described the first machine perfusion protocols applied to large animal VCA 27 , 28 , 36 , 39 , 44 46 . Nonetheless, current dynamic hypothermic and SNMP techniques are limited to preservation periods of 24 to 36 h due to factors such as edema and vascular resistance 34 , 47 49 . Supercooling has proven itself a promising technique to overcome these limits and go beyond several days in liver 22 , 50 .…”
Section: Discussionmentioning
confidence: 99%
“…So far, a few teams only used HMP, SNMP, and NMP techniques. Kruit et al have shown pioneering work with up to 36 h preservation of musculocutaneous VCA in a pig model using HMP ( 26 , 110 ). Pig hindlimbs were also successfully preserved for 24 h using SNMP before transplantation, as shown in our preliminary study ( 111 ).…”
Section: Supercooling Principles To Extend Organ Preservationmentioning
confidence: 99%
“…For flap models, Brouwers et al ( 64 ) perfused swine rectus abdominis myocutaneous flaps for 24 h at 10°C and reported a weight decrease in UW perfused flaps (−6% and −7%), whereas HTK perfused flaps had a 97% and a 60% increase in weight. After replantation and follow-up, both groups showed degenerative changes in muscle histology ( Table 2 ).…”
Section: Weight Gain and When To Stop Perfusionmentioning
confidence: 99%